Features of visualization of the lumbar spine in pathologies - Абрамова, Г. А. (ХНУРЕ, 2022)
A decrease in the biomechanical properties of vertebrae is a consequence of a violation of their morphological and functional integrity, which in turn causes deterioration, and in some cases leads to a critical state of the musculoskeletal system. In this paper, a set of experimental data was calculated for four cases: norm, osteoporosis, hemangioma, and multiple myeloma. This data allows you to classify the primary image according to the selected characteristics.
Keywords: morphological and functional integrity, vertebrae